Respiration Monitoring System of Lung Phantom Using Magnetic Sensor - Imamul Muttakin; David Abraham; Rocky Alfanz; Rohmadi Rohmadi (Institute of Advanced Engineering and Science, 2018)
Monitoring vital signs is substantial in healthcare to assist both diagnosis and treatment. This work proposes a means of telemonitoring system at initial stage to observe respiratory pattern on lung phantom. Magnetic sensor module LDC1000 is used to read inductance value of conductive material in relation to distance variation. Therefore, respiration pattern can be observed. In continuous mode, the inspiration inductance value is 8 uH, while expiration is 17 uH, with stoppage is 17 uH. For static measurement, the inspiration inductance value is 7.80 uH, while expiration is 16.46 uH and stoppage is 16.46 uH. Those values could be further referred for vital signs telemonitoring system design based on contactless and portable devices.